PEDAGOGICAL BASIS OF DEVELOPING MEDIA LITERACY SKILLS IN FUTURE HISTORY TEACHERS (TAMADDUN NURI JURNALI, 2025)
The article explores the pedagogical foundations of developing media literacy among future history teachers. It highlights the importance of integrating critical media analysis, source evaluation, and digital competencies into teacher training. Special emphasis is placed on historical thinking, working with historical sources, identifying misinformation, and fostering a responsible information culture through innovative teaching methods and digital tools.